Influencia del agregado reciclado sobre la compresión, abrasión, asentamiento y permeabilidad en el concreto permeable no estructural - Collantes Delgado, Jordy Alexis (2018)
In this research the influence of the replacement percentage of recycled concrete on settlement, the compressive strength of concrete, abrasion testing and permeability in processing of non-structural permeable concrete was evaluated. As a search for alternatives that improve the impact of concrete waste as a contaminant on human health and the environment, it is proposed to achieve a more sustainable construction model with the use of recycled concrete to produce non-structural permeable concrete with lower costs of production and improved properties. The purpose of the research was to determine the optimum percentage of recycled concrete that should replace the coarse aggregate in the design of a conventional mixture to form permeable concrete. The granulometries evaluated of the recycled concrete passes the mesh Nº4 and retains in the mesh Nº10; using replacement percentages of 30, 35, 40, 45, and 50%, with a dosage of Type MS cement, coarse aggregate and water / cement ratio of 0.45. The fresh concrete settlement test was performed under the ASTM C143 standard. In addition, three tests were carried out for the concrete in the hardened state: the compressive strength according to the ASTM C39 standard, the abrasion making use of the ASTM C1747 standard and the permeability according to the ACI 522R-10 standard. The specimens for the tests of the concrete in the hardened state were tested at ages of 28 days of curing, with the exception of the compression resistance test, in which they were also tested at ages of 7 days of curing. The optimal design of non-structural pervious concrete with recycled concrete was achieved with a percentage of 40%, presenting the maximum resistance to compression and an improvement of 36%, with respect to the design resistance. In addition to having optimal properties of settlement, abrasion and permeability.